THE APPLICATION OF ZEOLITE TO INCREASE NITROGEN USE EFFICIENCY IN CORN VEGETATIVE GROWTH IN COASTAL SANDY SOILS - Budiyanto, Gunawan (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2020)
Coastal sandy soil is usually dominated by sand fractions, having no micro pore complex that can bind water and store fertilizer nutrients. The application of zeolite rocks into the root zone of plants growing in sandy soil is expected to reduce nitrogen nutrient leaching.The research was carried out by using the greenhouse experiment method, arranged in a factorial completely randomized design. The first factor was activated zeolite rock doses, consisting of 7 levels, namely 0% (Z0), 1% (Z1), 2% (Z2), 3% (Z3), 4% (Z4), 5% (Z5), and 6% (Z6) per 10 kg of coastal sandy soils as planting media. Meanwhile, the second factor was nitrogen fertilizer doses, consisting of 3 levels, namely 75 kg (N1), 100 kg (N2), and 125 kg (N3) per hectare. The results showed that the application of zeolite rock to the planting media could increase the growth of corn plants fertilized with nitrogen. The best vegetative growth was obtained when 6% zeolite per 10 kg of planting media was applied. The application of 6% zeolite together with 125 kg per hectare N fertilizer resulted in the heaviest fresh plant biomass. The use of zeolite can increase the N-fertilizer uptake efficiency in the vegetative growth of corn plants grown in coastal sand soils.